Cultural diversity in the construction of incentive systems in enterprises – literature review - Przysada, Paula (Różnorodność kulturowa a konstrukcja systemów motywacyjncych w przedsiębiorstwach – przegląd literatury, 2019)
The aim of the work is to emphasize the importance of cultural diversity in the process of creating motivational systems. Therefore, selected definitions of motivation and incentive systems are collected and discussed in the article. The reason for their functioning in enterprises is to motivate employees and improve their work with financial and non financial incentives. Motivation is defined as the internal state of human being, which consists of feeling the lack of meeting the needs. In turn, motivating is an element of management that consists of using motivators in such a way that they ensure employees’ engagement for the organization’s aims, encourage employees to raise their qualifications and give them job satisfaction.This article also defines formal and informal institutions that are relevant to the operation of incentive systems. This work is based on literature review
Ekonomia XXI Wieku = Economics of the 21st Century, 2019, Nr 2 (22), s. 98-110
Keywords: incentive systems; motivators; international entreprises; system motywacyjny; motywatory; przedsiębiorstwa międzynarodowe